A 9-YEAR-OLD GIRL WITH ACUTE MACULAR NEURORETINOPATHY. (2018) - Rodríguez-Vargas, Gabriel; Gutiérrez-Hernández, Juan C.
Abstract : Purpose: To report the clinical findings of the youngest confirmed case of acute macular neuroretinopathy to the best of our knowledge. Methods: A 9-year-old patient describing a paracentral scotoma with a normal clinical examination and normal fluorescein angiography. Results: Initial fundus examination was unremarkable. Fluorescein angiography findings showed no abnormalities but scotoma was confirmed using Amsler grid. Optical coherence tomography showed a parafoveal hyperreflective band in the outer layers. Subsequent optical coherence tomography showed resolution of the pathology. Conclusion: Acute macular neuroretinopathy is a rare condition usually presented as paracentral scotomas. Optical coherence tomography and Amsler grid testing can be used for diagnosis and to monitor findings on follow-up until resolution. Abstract : To report and discuss the clinical findings of the youngest confirmed case to the best of our knowledge of acute macular neuroretinopathy.